Organizational attachment constrained by an instrumental business tradition: A review of the literature - Cifuentes-Leiton, Diana Milec (Revista Colombiana de Ciencias Sociales, 2026)
Currently, due to the various ways of organizing work and the modalities in which they are presented, it is necessary to reexamine the link that, as a concept, allows us to understand a social relationship, in this case, the one that workers forge with their work. The objective of this literature review article is to analyze the traditions from which the concept of organizational links has been approached in the scientific world. Using the Scopus database and Tree of Science procedures, a qualitative literature review was conducted using the meta-narrative method, with RAMESES protocol quality criteria, on a corpus of 87 documents to which content analysis and descriptive statistics were applied. It was found that in the last two decades, the concept of bonds has become relevant again in the research world, but its history shows that its dominant epistemological tradition is organizational behavior, from which knowledge of bonds is useful for the profitability of the company. From the perspective of organizational and work psychology, the effects of this tradition were critically discussed, especially when considering work modes other than employment, face-to-face presence, and attendance at a physical location, noting possibilities for new research agendas to theorize the bond as a social relationship in the work experience, without reification or instrumentalization.